PENGARUH UKURAN PERUSAHAAN,KOMPLEKSITAS OPERASI PERUSAHAAN, JENIS INDUSTRI, PROFITABILITAS, DAN SOLVABILITAS TERHADAP AUDIT DELAYPADA PERUSAHAAN CONSUMER GOODS INDUSTRI DAN PERBANKAN YANG TERDAFTAR DI BURSA EFEKINDONESIA (BEI) PERIODE 2013 – 2016. - Windi Risilaningtyas1, 12 .05 .52 .0230; Wahyudi, Djoko Wahyudi2 (Students' Journal of Accounting and Banking, 2018)
This study aims to determine the effect of company size, company size complexity, industry type, profitability, and solvency on consumer good industry and banking companies listed on the Indonesia Stock Exchange. The population used in this study are banking companies and consumer goods industries listed on the Indonesia Stock Exchange during the study period, namely from 2013-2016. The sample selection in this study was conducted based on purposive sampling method. The results of the firm size study, the complexity of the company's operations, and solvency have an effect on audit delay. The type of industry and profitability have no effect on audit delay. Keywords: Company Size. The complexity of the Company's operations, type of industry, profitability, solvency